Factors associated with self-care among black college students (Research, Society and Development, 2024)
Objective: To analyze the factors associated with self-care among black university students at a public university in the interior of Bahia. Method: It is a cross-sectional study with primary data collection carried out with 227 pedagogy students who self-identify as black. The instruments used in data collection were: a about profile sociodemographic questionnaire, a questionnaire that addresses issues relating to health behavior and the Nola Pender health promotion scale. Results: The following associations were evident: university students who said they eat better are those who take the most care of their health, according to the scale (p=0046); and those who exercise more take more care of their health when compared to those who exercise less (p= 0.006). Conclusion: It was possible to infer that black university students, despite their busy routine, have understood the importance of self-care by adopting practices that are beneficial to their health.